2002
DOI: 10.1542/peds.109.2.e20
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Morbidity After the Short-Term Use of Ibuprofen in Children

Abstract: ABSTRACT.Objective. To test the hypothesis that short-term use of ibuprofen increases asthma morbidity in children.Methods. A randomized, double-blind, acetaminophen-controlled clinical trial was conducted. Children who had asthma and a febrile illness were randomly assigned to receive either acetaminophen suspension or ibuprofen suspension for fever control. Rates of hospitalization and outpatient visits for asthma during follow-up were compared by randomization group.Results. A total of 1879 children receivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
131
2
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(137 citation statements)
references
References 15 publications
2
131
2
2
Order By: Relevance
“…To determine the effects of the medicines on asthma in one study, 72 a subgroup analysis was performed to determine the safety of paracetamol and ibuprofen in the 1879 children with asthma 73 (defined as those receiving β-agonists, theophyllines or inhaled steroids on the day before trial recruitment). The authors found no evidence of increased hospital admissions or outpatient attendances for asthma associated with ibuprofen compared with paracetamol.…”
Section: Serious Adverse Eventsmentioning
confidence: 99%
“…To determine the effects of the medicines on asthma in one study, 72 a subgroup analysis was performed to determine the safety of paracetamol and ibuprofen in the 1879 children with asthma 73 (defined as those receiving β-agonists, theophyllines or inhaled steroids on the day before trial recruitment). The authors found no evidence of increased hospital admissions or outpatient attendances for asthma associated with ibuprofen compared with paracetamol.…”
Section: Serious Adverse Eventsmentioning
confidence: 99%
“…11 There is, however, significant controversy regarding the importance of these challenge-derived findings for selected patients in the routine treatment of children with asthma. Lesko et al 12 showed a decrease in outpatients visits for asthma exacerbations among asthmatic children after short-term use of ibuprofen and definitely no increase in the rate of hospitalization for these children. A recent review of the subject even suggested that ibuprofen, as an antiinflammatory medication, may be of use in the treatment of acute exacerbations among asthmatic children 13 In recent years, a new classification of NSAID hypersensitivity has been proposed 14 and extended to the pediatric age group.…”
mentioning
confidence: 98%
“…The standard clinching way to assess causality Table 1 The consistency of interdisciplinary evidence makes the causal association between asthma and acetaminophen plausible enough to change prescription practice (in paediatrics): McBride (2011) 1. Strength of the association [57][58][59] 2. Robustness of association across geography, culture and age [51,[53][54][55][60][61][62][63] 3.…”
Section: Case Study: the Paracetamol Enigma In Asthmamentioning
confidence: 99%
“…Robustness of association across geography, culture and age [51,[53][54][55][60][61][62][63] 3. Dose-response relationship between acetaminophen exposure and asthma [58,59] 4. Coincidence of time trends in acetaminophen use and asthma increase [64] 5.…”
Section: Case Study: the Paracetamol Enigma In Asthmamentioning
confidence: 99%